A qualitative examination of urban vs rural sustainable consumption behaviours of energy and water consumers in the emerging Egyptian market. Issue 2 (15th November 2019) - Marzouk, Omneya A.
Abstract : Purpose: The study aims to investigate the differences among urban and rural consumers in terms of their energy and water sustainable consumption behaviour levels and drivers and also empirically blueprint conceptual frameworks highlighting urban and rural consumer drivers to consume sustainably. Design/methodology/approach: This research follows an exploratory design using a qualitative approach; 14 in-depth interviews followed by one focus group were conducted with urban consumers; on the other hand, 18 in-depth interviews followed by one focus group were conducted with rural consumers. Findings: The findings show that no differences exist among urban and rural consumers in terms of both their sustainable consumption levels and their drivers to consume sustainably; such findings were encapsulated in the form of one conceptual framework pertinent to both urban and rural consumers; it has the following relevant factors: consumers' attitudes toward conservation, subjective norms, perceived behavioural control, self-preference, public media influence, perceived economic value and perceived moral obligation to be relevant antecedents of conservation behaviour, which – in turn – drives sustainable purchase behaviours with the moderating effect of socio-demographic variables. Originality/value: This paper contributes to extant literature as it provides evidence for the drivers of sustainable consumption behaviours of urban versus rural consumers in emerging countries; it also tentatively answers the question of whether the socio-demographic variables infer a difference in consumers' sustainable consumption; finally, it studies sustainable consumption from a novel perspective with a focus on the relationship between its two pillars.